Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes syndrome: a case report. (4th May 2023) - Ru, Yong-Xin; Ying, Li; Dong, Shu-Xu; Yi, Hui-Ming; Jing, Liu; Yongqiang, Zhang
ABSTRACT: A biopsy of gastrocnemius muscle from a patient with mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) syndrome was studied histologically in semithin sections stained by hematoxylin-and-eosin (H&E) and toluidine blue, and ultrathin sections by transmission electron microscopy (TEM). H&E stain demonstrated typical ragged-red fibers (RRFs) and affected fibers in fascicles. Toluidine-blue stain showed an irregular meshwork in the center of RRFs. TEM demonstrated damaged myofibrils and variations in mitochondrial structure in RRFs and affected fibers. Dense mitochondria were compacted with cristae and pleomorphic electron-dense inclusions. Lucent mitochondria included paracrystalline inclusions with a parking lot appearance. At high magnification, the paracrystalline inclusions were composed of plates that paralleled and connected with mitochondrial cristae. These observations indicated that electron-dense granular and paracrystalline inclusions resulted from cristal degeneration and overlapping in mitochondria in MELAS syndrome.